Proteins of insoluble matrix of avian (gallus gallus) eggshell - Miksík, Ivan; Eckhardt, Adam; Sedláková, Pavla; Mikulikova, Katerina (Connective tissue research, 2007)
The protein composition of the insoluble avian eggshell matrix was studied. The determination of these proteins insoluble in water (EDTA-insoluble) was carried out using enzymatic cleavage followed by a high-performance liquid chromatography-mass spectrometry method. The influence of various enzymes on the protein splitting also was studied. The distribution of proteins depends on the type of layer (localization within the eggshell): ovocalyxin-32 was found mainly in the outer layer (the cuticle); ovocleidin-116 and 17 and ovocalyxin-36 were found throughout the whole eggshell, whereas ovalbumin was only found in the inner layer, the mammillary. The pigment (protoporphyrin IX) was mainly found in the cuticle and is incorporated into the protein network.
Keywords: kur domácí; Animals; Egg Shell; Electrophoresis, Polyacrylamide Gel; Female; Edetic Acid; Electrophoresis, Capillary; Chickens; elektroforéza kapilární; ženské pohlaví; Protoporphyrins; Tandem Mass Spectrometry; vysokoúčinná kapalinová chromatografie; EDTA; Solubility; rozpustnost; protoporfyriny; vaječná skořápka; hmotnostní spektrometrie s elektrosprejovou ionizací; Chromatography, High Pressure Liquid; tandemová hmotnostní spektrometrie; Egg Proteins; vaječné proteiny; Amino Acids; zvířata; aminokyseliny; elektroforéza v polyakrylamidovém gelu; Spectrometry, Mass, Electrospray Ionization